Optimalisasi Metode Pembelajaran Al Quran Dalam Meningkatkan Minat Belajar Santri (Studi Kasus TPQ Al Iman Kelurahan Bandarkidul Kota Kediri) - Ulumiah, Fahimatul; Amanah, Siti (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2024)
this research is motivated by the lo interest in learning of students in the Al-Qur’an Al-Iman Education Park, Bandarkidul Village, Kediri City. Researchers suspect that many factors influence this, including  inadequate learning media, a less conducive learning environment, students with different learning characteristics and easily bored, and the application of learning methods that are less than optimal. The objectives of this research are; 1) to find out the method of learning the Qur'an in increasing students' interest in learning at TPQ al-Iman; 2) to find out how to optimize the Qur'anic learning method to attract students' interest in learning at TPQ al-Iman. This study uses a qualitative descriptive method that performs analysis and direct observation at the research site which is located at TPQ al-Iman, Bandarkidul Village, Kediri City. The results of the research can be seen that the learning method applied in TPQ al-Iman, Bandarkidul Village, Kediri City, has been well prepared, but has not been maximized properly, so that students' interest in participating in learning is still relatively low. It is hoped that with this research, teachers/ustadz can apply this method of learning the Qur'an optimally and efficiently.